KOPERASI JASA KEUANGAN SYARIAH BAITUL MAAL WAT-TAMWIL (STUDI KASUS DI BERINGHARJO, YOGYAKARTA) - Umam, Khotibul (Jurnal Media Hukum, 2013)
Koperasi Jasa Keuangan Syariah Baitul Maal wat-Tamwil (KJKS BMT) is an organization that combines the concept of cooperatives and the concept of sharia. Both have the same spirit of kinship and mutual assistance (taâawun). The concept is realized in the form of maal products and tamwil products, and accompanying activities, giving the product in question. Operational KJKS BMT based on the laws and regulations in the field of cooperatives.